(3GdPNjQI aj eMGSf Cgd GdLRjQIs - (3Ydj Hf HSGe GdTfJQjfj GdCfOdSj, CHh GdMSf,J (B542 (3g` s
(3ChdgG (B:s
(3aUd ai PcQ GdCYjGf hGdeTGgjQ hgh GdLGfH GdYQHi ef LRjQI GdCfOdSi s
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B43s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(7753) s
Keywords: (3GdCOHs